FULLY-STEEL ALLOYS WITH INCREASED CAVITATION-EROSION PROPERTIES - M. I. Karpenko; V. M. Karpenko; O. D. Kudrjavtsev (Литьë и металлургия)
In the work the research of influence of the complex alloy addition as well as the additional microalloying by ligature NbVA, by zirconium nitride and ferrotitanium on the structure, mechanical and cavitation-erosive qualities of steels.